The Learning Style-Based Learning Media to Improve Hindu Religious Learning Outcomes Class XI SMAN Purwoharjo - Ratna Mei Vidia; I Wayan Sukra Warpala; I Kadek Suartama (Jurnal Penelitian Pendidikan IPA, 2025)
The low learning outcomes of Hindu Religious Education at SMAN Purwoharjo are shown by 72.5% of 40 grade XI students obtaining scores below KKTP (75). This condition is influenced by the lack of learning innovation, assessments that have not accommodated learning styles, and the limited use of technology-based media. This research aims to develop and test the validity, practicality, and effectiveness of learning style-based learning media to improve learning outcomes as well as describe its implementation. The research uses the ADDIE development model with the subject of grade XI students. Research instruments include validation of content, design, and media by experts, individual and small group trials for practicality, and pretests for effectiveness. Data analysis was carried out in a quantitative descriptive manner by calculating the percentage of validity, practicality score, and improvement of learning outcomes. The development process includes the stages of analysis, design, development, implementation, and evaluation. The validation results showed that the media was very valid with a content score of 91%, design of 88%, and media of 90%. Practicality is rated very good with an average of 88%. Effectiveness was shown through an increase in students' average scores from 68.5 to 83.7 and an increase in completeness by 22.19%. This media integrates learning style assessments, selection of materials according to profiles, technology-based interactive activities, and feedback between teachers and students. The results of the study prove that learning style-based learning media is effective in improving learning outcomes while creating an interactive and fun learning atmosphere.